2022
DOI: 10.1007/s10508-021-02279-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Changes in Sexual Interest and Distress About Discrepant Sexual Interest During the First Phase of COVID-19 Pandemic: A Multi-Country Assessment in Cohabiting Partnered Individuals

Abstract: Due to COVID-19 pandemic, different restrictive measures in terms of physical distancing and lockdowns have been introduced in most European countries, affecting all facets of social life. Currently, little is known about how partnered individuals perceive changes in their sexual life during this complex emergency. This study explored retrospectively assessed changes in sexual interest for one’s partner and levels of distress related to perceived sexual interest discrepancy during the first phase of the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…It is also important to note that some other studies reported positive changes in sexual behavior [38][39][40][41][42][43] and higher assessment of sexual satisfaction [42,44] during the COVID-19 pandemic. Arafat et al [38] found that 45% of the respondents from three Asian countries (Bangladesh, India and Nepal) reported that the lockdown impacted their sexual life.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also important to note that some other studies reported positive changes in sexual behavior [38][39][40][41][42][43] and higher assessment of sexual satisfaction [42,44] during the COVID-19 pandemic. Arafat et al [38] found that 45% of the respondents from three Asian countries (Bangladesh, India and Nepal) reported that the lockdown impacted their sexual life.…”
Section: Discussionmentioning
confidence: 96%
“…A decrease in sexual satisfaction was reported during the pandemic (when compared to pre-pandemic time) among healthcare professionals from Brasil [17], adults from Egypt [24], France [25], Germany [28], Kenya [37], and Singapore [33]; among patients with infertility from China [19]; and among women from Poland [31], Italy [30], and the USA [35]. By contrast, in comparison to the period before the pandemic, the frequency of sexual activity increased during the lockdown in Bangladesh, India, Nepal [38], China [39], Singapore [40], in seven countries of the European Union (the Czech Republic, Croatia, Germany, Portugal, the Netherlands, France and Sweden) and Turkey [41], in a nationwide sample of men from Germany [42], and in a large convenience sample of men from the United States of America [43]. Self-reported sexual satisfaction did not change between waves of the COVID-19 pandemic among adults from Canada [18] and China [39].…”
Section: Introductionmentioning
confidence: 99%
“…There are also a few very unique longitudinal studies [ 5 , 32 ]. International projects, the results of which are just beginning to be announced, have to be considered a valuable initiative [ 23 , 35 ]. Our analyses based on 6440 records, in total across three waves, provided an opportunity to address the pre-pandemic period while also showing trends in the months ahead.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of the above components of sexual life were analyzed in relation to the pandemic period [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The contributions came from various countries, including Poland [ 19 , 25 , 29 , 30 , 31 , 32 , 33 , 34 ], sometimes based on multi-country projects [ 8 , 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the more satisfied a couple is, the more likely they engaged in a collaborative approach to prevention, emphasizing the importance of relationships in prevention of COVID-19 spread. Štulhofer et al ( 2022 ) found that a little over half of participants reported no change in their sexual interest during the pandemic and this was similar across seven European Union countries and Turkey. Additionally, this study found that distress around desire discrepancy between partners was associated with coping with and worrying about the pandemic, relationship quality and emotional closeness, and motivation for sex.…”
mentioning
confidence: 95%